Compulsory licensing of standard-essential patents and injunctive relief as abuse of dominant position in violation of Article 102 TFEU - Pitkämäki, Petteri (fi=Turun yliopisto|en=University of Turku|, 2016)
When a dominant undertaking holding a standard-essential patent uses its exclusive right to the IP to seek injunctions against those wishing to produce either de jure or de facto standard compliant products, it creates a conflict between the exclusive right to the use of the IP on the one hand and the possible abuse of dominance due to the exclusionary conduct on the other. The aim of the thesis is to focus on the issues concerning abuse of dominance in violation of Article 102 TFEU when the holder of the standard-essential patent seeks an injunction against a would-be licensee. The thesis is mainly based on the most recent ECJ case law in Huawei and the Commission’s recent decisions in Samsung and Motorola. The case law in Europe prior to those decisions was mainly focused on the German case law from Orange Book Standard which provided IP holders great leverage due to the almost automatic granting of injunctions against infringers. The ECJ in Huawei set out the requirements for when a de jure standard-essential patent holder would not be violating Article 102 TFEU when seeking an injunction, requiring that negotiations in good faith must take place prior to the seeking of the injunction and that all offers must comply with FRAND terms, thus limiting the scope of case law derived from Orange Book Standard in Germany. The ECJ chose not to follow all of the reasoning the Commission had laid out in Samsung and Motorola which provided a more licensee-friendly approach on the matter, but rather chose a compromise between the IP holder friendly German case law and the Commission’s decisions. However, the ECJ did not disclose how FRAND terms themselves should be interpreted, but rather left it for the national courts to decide. Furthermore, the thesis strongly argues that Huawei did not change the fact that only vertically integrated IP holders who have made a FRAND declaration are subject to the terms laid out in Huawei, thus leaving non-practicing entities such as patent trolls and entities that have not made a FRAND declaration outside its scope. The resulting conclusion from the thesis is that while the ECJ in Huawei presented new exceptional circumstances for when an IP holder could be abusing its dominant position when it seeks an injunction, it still left many more questions answered, such as the meaning of FRAND and whether deception in giving a FRAND declaration is prohibited under Article 102 TFEU or not.